Character Design Concept Art for a Cyberpunk Themed Story - Abiel Bintoro, Christopher; Septian Rachman, Vicky (International Journal of Art, Design, and Metaverse, 2023)
Character design is a form of illustrative artwork used to visualize characters for films, games, and animations. These designs serve as the foundation for creating the final characters in various media. However, in today’s film industry, artistic aspects are often overshadowed by commercial interests, leading to a lack of appreciation for creative concepts. To address this, concept art should be recognized and utilized as a guiding force in filmmaking. Cyberpunk, a captivating science fiction genre, explores a future where humans merge with machines, losing their humanity. The author will focus on character concept art aligned with the Cyberpunk theme, supporting the film industry in visualizing characters. Through Cyberpunk character design, writers can transform their once-dreamt ideas into impactful works of art, appreciated by audiences worldwide.